IN-VITRO SCREENING OF MALAYSIAN HONEY FROM DIFFERENT FLORAL SOURCES FOR ANTIBACTERIAL ACTIVITY ON HUMAN PATHOGENIC BACTERIA - Ng, WenJie; Ken, Khai-Wei; Kumar, Roshani-Vijaya; Gunasagaran, Hemamalani; Chandramogan, Vanaysha; Lee, Ying-Yee (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Different researches on therapeutic effects of honey have been conducted in different regions; however the study on the potential antibacterial activity of Malaysian honey is still limited. In this study, antibacterial activities of different monofloral honey samples were tested against several common human pathogenic bacteria. Materials and Methods: The well-diffusion method, minimum inhibitory concentrations (MIC) and minimum bactericidal concentration (MBC) techniques were employed to investigate the putative antibacterial activity of Malaysian monofloral honey from Koompassia excelsa (Becc.) Taub (Tualang), Melaleuca cajuputi Powell (Gelam) and Durio zibethinus Murr. (Durian). Honey samples were tested against Staphylococcus aureus ATCC6518 and ATCC25923, Staphylococcus epidermidis ATCC12228, Enterococcus faecium LMG16192, Enterococcus faecalis LMG16216 and ATCC29212, Escherichia coli ATCC25922, Salmonella enterica serovar Typhimurium ATCC14028 and Klebsiella pneumoniae ATCC13883. Results: Marked variations were observed in the antibacterial activity of these honey samples. Durian honey failed to produce substantial antibacterial activity, whereas Tualang and Gelam honey showed a spectrum of antibacterial activity with their growth inhibitory effects against all of the tested bacterial species including vancomycin-resistant enterococci (VRE). Conclusion: Present findings suggested Gelam honey possesses highest antibacterial effect among the tested Malaysian honey samples.